1958
DOI: 10.3402/tellusa.v10i4.9264
|View full text |Cite
|
Sign up to set email alerts
|

Natural Sources of Gaseous Pollutants in the Atmosphere

Abstract: Various gaseous pollutants including ozone, nitrous oxide. nitric oxide, nitrogen dioxide, methane. hydrogen, formaldehyde, ammonia, hydrogen sulfide, mercaptans, chlorine compounds and free radicals can be formed by natural processes such as ultraviolet photochemical processes in the upper atmosphere and microbiological processes. The modes of formation and destruction of these gases, especially of their concentrations in the atmosphere, and the various reactions in which these gases can participate with each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1960
1960
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…In nature biological processes produce nitrite which in acid conditions leads to the release of NO X . 10 The NO is rapidly oxidized by O 3 to NO 2 (k ~10 7 1 mol" 1 sec" 1 ). 11 " Nitrogen dioxide is oxidized by O 3 more slowly than NO, but still very rapidly (k ~2-4 X 10 4 1 mole" 1 sec -1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In nature biological processes produce nitrite which in acid conditions leads to the release of NO X . 10 The NO is rapidly oxidized by O 3 to NO 2 (k ~10 7 1 mol" 1 sec" 1 ). 11 " Nitrogen dioxide is oxidized by O 3 more slowly than NO, but still very rapidly (k ~2-4 X 10 4 1 mole" 1 sec -1 ).…”
Section: Resultsmentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27] The incorporation of ClNO 2 into large-scale atmospheric models suggests that nitryl chloride may have a significant impact upon Cl radical formation and atmospheric oxidative chemistry. 31 Early experiments with relatively high levels of NO 2 reacting with wet or dry NaCl showed the formation of ClNO. ClNO is a known product of the reaction of chloride ion with sym-N 2 O 4 (dimer of NO 2 ) 30 and its release into the atmosphere was suggested from the reaction of moist NaCl with nitrogen dioxide.…”
Section: Introductionmentioning
confidence: 99%
“…65 Other studies, however, have indicated a net movement of atmospheric sulfur from the oceans to terrestrial environments via H 2 S, 63 and other studies have indicated the net movement of atmospheric sulfur from terrestrial environments to the oceans, the vehicle being H 2 S. 62 In any event, (CH 3 ) 2 S is biotically produced in the oceans. Marine algae, such as Polysiphonia fastigiata, P. nigrescens, 66 Laminaria sp., 65 Cyclotella nana, 61 Gyrodinium cohnii, 61>6& Syracosphaera carterae, Skeletonema costatum, Amphidinium carteri, Phaeodactylum tricomutum, Cyclotella cryptica, and Tetraselmis sp., 69 all evolve (CH 3 ) 2 S. Soils are also a source of atmospheric (CH 3 ) 2 S 6 5 ' 7°>7 ' and methyl mercaptan (methanethiol) (CH3SH). 70 70 Similarly, Aspergillus niger, Micromonospora gypseum, and Scopulariopsis brevicaulis also metabolize methionine, with the subsequent release of CH3SH.…”
Section: (4)mentioning
confidence: 99%
“…26 An estimated 5.69 X 10 8 tons/year of CO can be removed by the total soil surface of the continental U.S. 27 Several algae and bacteria metabolize CO and, therefore, have the potential of acting as additional biotic sinks. The CH 4 producers Methanobacterium formicicum and Methanosarcina barkerii, are able to utilize CO, 76 (17); brown algae (10-12); green algae (23); bluegreen algae (22, 23) Bacteria (33,37,61,77) Bacteria (61,77,83,(85)(86) Fungi ; actinomycetes (5,02-506); bacteria (109,(508)(509) bacterium isolated from sewage sludge, metabolizes CO according to: 111 ' 112 …”
Section: B Microbes As Sinks For Gaseous Atmospheric Pollutantsmentioning
confidence: 99%